Psycho-pious motivations and Muslim migration to the West : the case of Singaporean Malay-Muslims in Melbourne, Australia - Syed Khairudin Aljunied,; Abbas Khan, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Muslim migration to the West has witnessed a surge in the last few decades in light of a host of crises and conflicts that have been taking place across the Muslim world. This article analyses the case of a group of Muslims from a stable and highly-developed country that similarly took the life-changing step of migrating to the West. We argue that one of the crucial factors that have driven Malay-Muslims from Singapore to migrate to Australia is what could be termed as “psycho-pious motivations.” By this, we mean motivations that are borne out of a negative psychological context and of being in a disadvantaged position when it comes to religiosity, thus generating the desire to relocate to a different country where a better life and the freedom to enliven one’s religiosity can be fully realized.